2020
DOI: 10.3390/nano10040737
|View full text |Cite
|
Sign up to set email alerts
|

Droplet Coalescence by Selective Wettability Enhancement in Microfluidic Devices

Abstract: A new approach for droplet coalescence in microfluidic channels based on selective surface energy alteration is demonstrated. The proposed method involves patterning the surface of cyclic olefin copolymer (COC), a hydrophobic substrate attached to a polydimethylsiloxane hydrophobic microchannel, with graphene oxide (GO) using standard microfabrication techniques. Surface wettability and adhesion analyses confirmed the enhancement of the COC surface energy upon GO patterning and the stability of the GO film on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…Due to the presence of oxygen functional groups that form hydrogen bonds, GO is known to have hydrophilic characteristics, resulting in low contact angles [ 22 , 23 ]. By reducing GO to rGO form, the hydrophobicity of the material is increased, hence increasing the contact angle between water droplets and GO surfaces [ 24 ].…”
Section: Resultsmentioning
confidence: 99%
“…Due to the presence of oxygen functional groups that form hydrogen bonds, GO is known to have hydrophilic characteristics, resulting in low contact angles [ 22 , 23 ]. By reducing GO to rGO form, the hydrophobicity of the material is increased, hence increasing the contact angle between water droplets and GO surfaces [ 24 ].…”
Section: Resultsmentioning
confidence: 99%
“…In our recent work [ 3 , 4 , 19 ] we have shown that treating COC with O 2 /Ar plasma followed by spin coating with GO dispersions resulted in stable GO coatings. Here, we investigated whether there is an apparent effect of plasma treatment on the wettability of the COC after the GO deposition.…”
Section: Resultsmentioning
confidence: 99%
“…First, the COC substrate was cleaned using isopropanol and DI. Next, the substrate was treated with an argon/oxygen low pressure inductive plasma (HARRICK PLASMA, Model: Expanded plasma cleaner/PDC-002, Ithaca, NY, USA) for a fixed duration (5, 20, 60 and 120 min) to increase the surface energy of the substrate and enhance the bonding between GO and COC substrate [ 19 ]. Plasma treatment was performed at a pressure of 626 mtorr, gas flowrates of 1–2 scfh, and a maximum power of 29.6 W with radio frequency (RF) of 12 MHz.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Scenarios of microscale and nanoscale droplet collision dynamics have been widely investigated by either experiments or numerical simulations. Nahla et al [ 10 ] demonstrated a new approach for droplet coalescence in microfluidic channels based on selective surface energy alteration, which focused on the coalescence process of the micro-nano droplet. Lian et al [ 11 ] experimentally investigated the bouncing dynamics of impact droplets on the superhydrophobic surfaces for shortening contact time, and established the relationship between Weber number and contact time to find the minimum Weber number that formed the pancake-like bouncing behavior.…”
Section: Introductionmentioning
confidence: 99%